Stereoisomerism in pentaerythritol-bridged cyclotriphosphazene tri-spiranes: Spiro and Ansa 1,3-propanediyldioxy disubstituted derivatives [2] - Uslu, Aylin; Coles, Simon J.; Davies, David B.; Eaton, Robert J.; Hursthouse, Michael B.; Kılıç, Adem; Shaw, Robert A. (Wiley-VCH Verlag, 2005)
[No abstract available]
Keywords: Cyclotriphosphazene derivatives; Trispiranes